Haplodiploidy, sex-ratio adjustment, and eusociality. - Gardner, A; Ross, L (2013)
Hamilton's "haplodiploidy hypothesis" holds that inflated sororal relatedness has promoted altruistic sib rearing in haplodiploids, potentially explaining their apparent predisposition to eusociality. Here, we suggest that haplodiploidy may instead promote eusociality simply by facilitating sex-ratio adjustment. Specifically, haplodiploidy may enable sex-ratio bias toward the more helpful sex, owing to "local resource enhancement," and such sex-ratio bias may promote the evolution of helping by individuals of that sex, owing to the "rarer-sex effect." This could explain why haplodiploidy appears to have been important for eusociality in taxa with only female helpers, such as ants, wasps, and bees, but not in taxa with both male and female helpers, such as termites.